2019
DOI: 10.2340/16501977-2514
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short- and mid-term outcomes of Italian- and German-speaking patients after an interdisciplinary pain management programme in Switzerland: A prospective cohort study

Abstract: This study examined the health of patients with chronic pain who participated in a specific rehabilitation programme for chronic pain. Patients' health was measured before participating in the programme, at the end of the programme, and after the programme. German-speaking patients were compared with Italianspeaking patients. Both groups participated in the same pain management programme with the same therapies, held either in German or in Italian. Italian-speaking and German-speaking patients improved immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(42 reference statements)
2
7
0
Order By: Relevance
“…The fact that the IPR-LI group showed a significantly worse health situation before the programme compared with the reference group is in line with other studies of patients participating in interdisciplinary pain rehabilitation programmes ( 25 , 26 ) and studies of immigrant patients with pain ( 27 ). In a Swedish population-based study ( 27 ), a poor health-related situation for immigrant patients was described, including an increased risk for immigrants of developing different sorts of pain, mediated by their state of mood.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The fact that the IPR-LI group showed a significantly worse health situation before the programme compared with the reference group is in line with other studies of patients participating in interdisciplinary pain rehabilitation programmes ( 25 , 26 ) and studies of immigrant patients with pain ( 27 ). In a Swedish population-based study ( 27 ), a poor health-related situation for immigrant patients was described, including an increased risk for immigrants of developing different sorts of pain, mediated by their state of mood.…”
Section: Discussionsupporting
confidence: 88%
“…In a study based on the SQRP registry, patients who were born outside Europe, of both sexes and different educational levels, were found to be the group with the poorest situation before the programme, based on pain intensity, depression, anxiety and health-related quality of life ( 25 ). Also, when the different patient groups are European, the non-native patients have been shown to have less favourable health ( 26 ). In this Swiss study by Benz et al ( 26 ), immigrant patients (Italian-speaking) showed worse self-reported health compared with native patients (German-speaking) before the programme.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the initial project in the mid 1990s, evidence of validity was still thin on the ground and further literature, especially on recommended core sets, did not exist. After the first phase of the project, the choice of measures was revised on the basis of the results of the previous studies in our institution [19][20][21][22]. In particular, relative weak responsive scales were eliminated [22].…”
Section: Methodsmentioning
confidence: 99%
“…Sociodemographic and potentially confounding parameters, such as age, gender, occupation (working capacity), living conditions, sports habits, and formal education, were recorded at admission to the clinic on a standardized form used in many previous studies [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Immigrants and refugees represent a growing portion of patients in primary health care (Allison et al, 2002;Brause et al, 2012). Both at group and individual levels they will explain ill-health in different ways, thus complicating the diagnostic process of, for example, non-European women with non-malignant widespread pain and long sickness absence (Aznar-Lou et al, 2017;Nyen and Tveit, 2018;Wang et al, 2019;Benz et al, 2019;Eid et al, 2019).…”
Section: Introductionmentioning
confidence: 99%